Adolescents' Social Emotional Health, Stress Resilience and Perceived Parenting Styles - Petrulyte, Ala; Guogienė, Virginija; Jakavičienė, Aušra (Advances in Social Sciences Research Journal, 2024)
The current study adopts a holistic and positive psychological approach to mental health, focusing on the emotional and social health domains of adolescents. The focus is on the correlation between adolescents' social emotional health, stress resilience and their perceived parenting style. Research methodologies: The Social Emotional Health Survey System (SEHS-S, Furlong et al., 2014); Brief Resilient Coping Scale (Sinclaire, Wallston, 2004); The parenting styles questionnaire (EMBU, Arrindell, 1999). Participants: 160 adolescents between 12 and 18 years of age. Research results: all parenting styles (except rejection) perceived by adolescents are significantly positively related to overall social emotional health (SEHS-S) index Covitality; adolescents stress resilience significantly positively correlates with all sub-scales of social emotional health and with the overall Covitality index. Effective communication between parents and children could help prevent or mitigate many problems and stresses during adolescence and contribute to positive development in adulthood.